PHYSICO-CHEMICAL REGULARITIES OF COMPOSITE COAGULANTS SYNTHESISED FROM LOCAL MINERAL RAW MATERIALS IN THE TREATMENT OF INDUSTRIAL WASTEWATER (International Conference on Education, Psychology and Humanities, 2026)
This thesis investigates the physico-chemical regularities of a composite mineral–organic coagulant obtained from local bentonite clay and sapropel (mass ratio 60:40) in the treatment of industrial wastewater. The mechanism of action is multistage: adsorptive capture is provided by the high specific surface area and cation-exchange capacity of bentonite, while the binding of organic particles is ensured by the humic substances of sapropel. The coagulation activity was compared with potassium–aluminium sulfate and iron(III) chloride. At an optimal dose of 100 mg/L and pH 6.8–7.4, turbidity removal reached 95.6 % and COD removal 71.4 %. Zeta-potential measurements showed a shift of the system towards the isoelectric zone through charge neutralisation. The results justify the development of an inexpensive, environmentally safe coagulant based on local raw materials.
Keywords: Composite coagulant, bentonite, sapropel, coagulation, zeta potential, adsorption, turbidity, chemical oxygen demand, industrial wastewater, local raw materials.